Cancer-Related Intracellular Signalling Pathways Activated by DOXorubicin/Cyclodextrin-Graphene-Based Nanomaterials - Rosamaria Pennisi; Maria Musarra-Pizzo; Tania Velletri; Antonino Mazzaglia; Giulia Neri; Angela Scala; Anna Piperno; Maria Teresa Sciortino (Biomolecules, 2022)
In the last decade, nanotechnological progress has generated new opportunities to improve the safety and efficacy of conventional anticancer therapies. Compared with other carriers, graphene nanoplatforms possess numerous tunable functionalities for the loading of multiple bioactive compounds, although their biocompatibility is still a debated concern. Recently, we have investigated the modulation of genes involved in cancer-associated canonical pathways induced by graphene engineered with cyclodextrins (GCD). Here, we investigated the GCD impact on cells safety, the HEp-2 responsiveness to Doxorubicin (DOX) and the cancer-related intracellular signalling pathways modulated by over time exposure to DOX loaded on GCD (GCD@DOX). Our studies evidenced that both DOX and GCD@DOX induced p53 and p21 signalling resulting in G0/G1 cell cycle arrest. A genotoxic behaviour of DOX was reported via detection of CDK (T14/Y15) activation and reduction of Wee-1 expression. Similarly, we found a cleavage of PARP by DOX within 72 h of exposure. Conversely, GCD@DOX induced a late cleavage of PARP, which could be indicative of less toxic effect due to controlled release of the drug from the GCD nanocarrier. Finally, the induction of the autophagy process supports the potential recycling of DOX with the consequent limitation of its toxic effects. Together, these findings demonstrate that GCD@DOX is a biocompatible drug delivery system able to evade chemoresistance and doxorubicin toxicity.